What works best for getting the unemployed back to work: employment services or small-business assistance programmes? Evidence from Romania - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2007)
Recent empirical evidence has found that employment services and small-business assistance programmes are often successful at getting the unemployed back to work. One important concern of policy makers is to decide which of these two programmes is more effective and for whom. Using unusually rich (for transition economies) survey data and matching methods, I evaluate the relative effectiveness of these two programmes in Romania. While I find that employment services (ES) are, on average, more successful than a small-business assistance programme (SBA), estimation of heterogeneity effects reveals that, compared to non-participation, ES are effective for workers with little access to informal search channels, and SBA works for less-qualified workers and those living in rural areas. When comparing ES to SBA, I find that ES tend to be more efficient than SBA for workers without a high-school degree, and that the opposite holds for the more educated workers.
Keywords: 330; Active labour market programmes; evaluation; propensity score matching; transition economies; treatment effects; Arbeitsmarktpolitik; Arbeitsvermittlung; Mittelstandspolitik; Rumänien